Low back pain in emergency ambulance workers in tertiary hospitals in China and its risk factors among ambulance nurses: a cross-sectional study - Qiong Zhang; Hongyun Dong; Chunji Zhu; Guangzeng Liu (BMJ Open)
Objective Low back pain (LBP) could cause serious consequences and has been shown to be prevalent among emergency ambulance workers. Studies on the prevalence of and risk factors for LBP among emergency ambulance workers are scarce in China. The study aimed to determine the prevalence of LBP among ambulance workers, including doctors, nurses and drivers, and to explore the risk factors for ambulance nurses’ chronic LBP (lasting for at least 3 months).Design Cross-sectional study.Setting Emergency ambulance systems from 38 tertiary hospitals in Shandong, China were selected by random cluster sampling.Participants A total of 1560 ambulance workers completed the study.Outcome measures A paper-based questionnaire that included the Nordic Musculoskeletal Questionnaire, which evaluated LBP, the Dutch Musculoskeletal Questionnaire, which assessed ergonomic factors, and the Job Content Questionnaire, which assessed stress, was used. Multivariate logistic regression analysis was conducted to quantify the association of potential risk factors with chronic LBP among ambulance nurses.Results The 1 year prevalence of LBP lasting for at least 24 hours, 7 days and 3 months was 86.1%, 50.6% and 21.1%, respectively, among 498 ambulance nurses; 70.5%, 36.4% and 15.8% among 519 doctors; and 57.5%, 23.8% and 12.3% among 543 drivers. The factors contributing to chronic LBP among ambulance nurses were the frequent bending of the trunk, heavy or awkward lifting, shift work, low job satisfaction, high psychological fatigue, high psychological job demand, low job control, low supervisor support, older age, female sex and obesity.Conclusions LBP was more prevalent among ambulance nurses than among ambulance doctors and drivers. Many factors, especially psychosocial and ergonomic factors, contributed to ambulance nurses’ chronic LBP. Comprehensive measures might be needed to control LBP.